Influence of homogeneity of mineral materials’ grading and dosing errors on the stability of asphalt concrete mixture composition - Sivilevičius, Henrikas (Journal of Civil Engineering and Management, 2003)
Errors of optimal composition asphalt concrete mixture designed in the laboratory and their importance for road construction are investigated. After the analysis of asphalt concrete production according to the traditional technology, factors influencing its structure, characteristics and quality are systematised. Mathematical models of dependence of medium quadratic deviations of siftings of finite dosed mineral materials through control sieves on the means of siftings are estimated by a regressive analysis. Variations of grading of hot fractions 0–5 mm and 5–15 mm as well as cold mineral powder sieved through technological sieves of mixing equipment and influence of errors of dosing these mineral materials in the produced mixture on the stability of quantity of containing mineral components (crushed stone, sand and mineral filler) are identified. The main trends of asphalt concrete structure and handling of its equipment methods improvement are presented. First Published Online: 26 Jul 2012